A Novel Protein Elicitor BAR11 From Saccharothrix yanglingensis Hhs.015 Improves Plant Resistance to Pathogens and Interacts With Catalases as Targets - Zhang, Yanan; Yan, Xia; Guo, Hongmei; Zhao, Feiyang; Huang, Lili (Frontiers in Microbiology, 2018)
Previously, we reported the biocontrol effects of Saccharothrix yanglingensis strain Hhs.015 on Valsa mali. Here, we report a novel protein elicitor BAR11 from the biocontrol strain Hhs.015 and its functions in plant defense responses. Functional analysis showed that the elicitor BAR11 significantly stimulated plant systemic resistance in Arabidopsis thaliana to Pseudomonas syringae pv. tomato DC3000. In addition, systemic tissues accumulated reactive oxygen species and deposited callose in a short period post-treatment compared with the control. Quantitative RT-PCR results revealed that BAR11 can induce plant resistance through the salicylic acid and jasmonic acid signaling pathways. Further analysis indicated that BAR11 interacts with host catalases in plant cells. Taken together, we conclude that the elicitor BAR11 from the strain Hhs.015 can trigger defense responses in plants.